Time-Driven Activity-Based Costing for Selling Price Determination: Evidence from Sambal Berkah Chips MSMEs in Sibolga, Indonesia - Nurazizah; Saparuddin Siregar; Marliyah (Jurnal Investasi Islam, 2026)
This research is conducted to examine the calculation of production costs and the application of the Time-Driven Activity-Based Costing (TDABC) method in setting the selling price of Berkah Sambal Chips MSME located in Sibolga City, Indonesia. The study adopts a qualitative approach with a case study design. Data were obtained through interviews, direct observations, and documentation. The results show that the traditional costing approach generates a total daily production cost of IDR 2,689,298.00, with a unit production cost of IDR 3,362.00 per package. In contrast, the TDABC method generated a total production cost of IDR 2,615,198.00 per day, with a cost of production of IDR 3,269.00 per package. The reduction in production costs occurred because TDABC allocates costs based on effective working time, resulting in a more accurate allocation of production costs. Applying a 30% markup, the TDABC method produced a selling price of IDR 4,717.00 per package. However, the enterprise maintained a selling price of IDR 5,000.00 per package to achieve a higher profit margin. These results indicate that the Time-Driven Activity-Based Costing (TDABC) method improves cost efficiency and offers a more precise foundation for setting selling prices in Micro, Small, and Medium Enterprises (MSMEs).